Performance study of a single cylinder diesel engine using diesel with Pongamia pinnata and Camelina sativa seed oil blends. (2020) - Murali, G.; Anusha, M.; Arunkumar, M.
Abstract: Current paper studies the renewable energy of Camelina sativa biodiesel fuel which is having new fuel properties. Here Camelina sativa seed oil and Pongamia with equal proportions was used in the form of blends at various proportions with diesel. The blending ratios were taken as 20%, 40%, 60%, 80%, and 100% respectively, used as fuel in a single cylinder four stroke diesel engine. Further the engine emissions of different fuel usage have been investigated. The results shows that SFC increased by 3.5% and brake thermal efficiency is decreased by 6%. The biodiesel reduced carbon monoxide by 5% compared to diesel, hydrocarbon emissions decreased by 4.1%.